Study on Food and Nutrition Services Quality Management Program: Assessing the Impact of Quality Management Programs on Food and Nutrition Services (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There are a range of Quality Assurance (QA) programmers available to the food industry, such as GMP (Good Manufacturing Practices), HACCP (Hazard Analysis. Essential Control Points), ISO (Standardization International Organization) standards. For food quality and safety assurance, these systems and their combinations are recommended. Agri-food production involves a particular approach in order to meet the desired level of quality. It is important to know to what degree the systems relate to the overall product quality and to balance the methods used to achieve the goals of quality and safety.